Continuous assessment practice in public and private schools in Lagos State (2012)
Continuous assessment practice was introduced into the Nigerian educational system about the year 1978. Since the inception of this assessment practice, it has come under various criticisms, especially in its conduct by teachers and the various schools concerned. From around 1998, continuous assessment scores from secondary schools were utilized by public examination bodies like WAEC and NECO as part of the final assessment of students for May/June senior school certificate examination on a ratio of 30:70 i.e. 30% for continuous assessment from schools and 70% from students ’ performance in SSCE. As a result of the utilization of continuous assessment scores from schools, there have been reported irregularities among public and private schools in the conduct of this assessment. This paper therefore, investigated the practice of continuous assessment in public and private secondary schools in Lagos State. The study is an expost-facto and the instrument used for data collection was a questionnaire. Simple percentage was used for data analysis. Findings from the study reveal that there is disparity in the practice of continuous assessment among schools in Lagos State. It was discovered that while some schools allocate 50% mark to continuous assessment and 50% to terminal examination, other schools allocate 10% mark to continuous assessment and 90% to terminal examination. The study also revealed that continuo us assessment practice in Lagos State is mostly centered on the cognitive domain of learning as against the practice of taking into cognizance other domains of learning, affective and psychomotor. The study, therefore, recommends that continuous assessment should be made to cover the three domains of learning. Also, there .should be uniformity in marks allocated to continuous assessment by schools. Furthermore, the study also recommends that regular training on continuous assessment should be organized for teachers at the secondary school level.